Features of accounting and information risk management in the conditions of impact of COVID-19 - V.K. Makarovych; O.O. Hryhorevska; N.S. Stoika (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The purpose of the article is to develop theoretical provisions and develop guidelines for improving approaches to accounting for risks of exposure to COVID-19 and disclosure of information about them in the reporting of economic entities. In the process of research the methods of observation, comparison, analysis, synthesis, generalization were used. The study is based on the hypothesis that high-quality accounting and information support will increase the validity, efficiency and analytical information about the risks of COVID-19 and their impact on business activities in accordance with modern management requirements, strengthening the responsibility of performers, improving management accounting. The article summarizes the approaches to the impact of uncertainty and risk on the accounting and analytical system of enterprises, which are considered in scientific circles by domestic researchers. The risks of the enterprise’s activity that are relevant in the conditions of the COVID-19 pandemic are highlighted: risks caused by restrictions by legislative and regulatory acts; risks due to the occurrence of obligations related to the production and sale of products, goods, works, services; risks of asset impairment; risks to the recognition and measurement of liabilities; risks of possible bankruptcy; investment risks. to identify risk and assess it, you can use the «triple method». It is established that the accounting and information support of risk management in the conditions of influence of COVID-19 includes: methodical support of risk accounting, analytical support, documentary support; display of information on risks in the reporting, which allowed developing a report on the risks of the impact of COVID-19 on the activities of the enterprise. The obtained results are the basis for bringing the system of accounting and analytical support to a qualitatively new level and will generate useful, truthful and relevant information for enterprise management in decision-making to minimize the impact of risks on business activities through COVID-19.